Preventive health services for young children in Israel: historical development and current challenges - Deena R. Zimmerman; Gina Verbov; Naomi Edelstein; Chen Stein-Zamir (BMC, 2019)
Abstract Purpose Pediatric preventive health services are delivered in many different formats throughout the world. In Israel, these services for young children are provided in designated Maternal Child Health Clinics (MCHC). The history and operation of Israel's MCHC have been described primarily in the Hebrew language medical literature with most of these reports being over a decade old. This paper provides an up to date summary of the evolution and current care in Israel's one-hundred-year old model for the provision of preschool preventive health services. As these clinics have been recognized by the World Organization as a model for emulation, it is important that such information be made available. Abstract body Israel's MCHC provide universal care to infants and preschool children (0-6 years), free of charge. These community-based clinics provide developmental surveillance, growth monitoring, and routine childhood immunizations. Anticipatory guidance is offered to families on topics including nutrition, parenting and child safety. Screening is also performed for maternal postpartum depression and family violence. Care is given by public health nurses working in collaboration with physicians. The vast majority (> 96%) of the country's children receive care in this system. Immunization coverage rates through this system are in line with World Health Organization guidelines - over 95% overall average nationally. Unfortunately, the allocated funding has not increased in proportion to the population growth. There is ongoing debate on the role of the national government in health services: should it be that of a direct services provider or focus on guidance and regulation of the health system. Conclusion MCHC well child care can help assure widespread provision of pediatric preventive health care. For this model to function, both its funding and content needs to be updated on an ongoing basis to reflect current preventive health care needs.